AB0148 T-cell phenotype and intracellular cytokine-production in t-cells in patients with systemic sclerosis. (23rd January 2014) - Klein, M.; Almanzar, G.; Höfner, K.; Schmalzing, M.; Kleinert, S.; Tony, H.-P.; Benoit, S.; Hamm, H.; Goebeler, M.; Prelog, M.
Abstract : Background: Systemic Sclerosis (SSc) is a disease with mostly unknown etiology. Until now, various cytokines have been identified that may play a role in the pathogenesis of the disease. Objectives: Our aim was to investigate the peripheral T-cell phenotype and intracellular cytokines in 27 SSc patients compared to 30 age-matched healthy donors (HD). Methods: Peripheral blood mononuclear cells (PBMCs) were isolated and characterized into naive (CD45RA+CD28+), central-memory (CD45RA-CD28+), memory/effector (CD45RA-CD28-) and terminally-differentiated T-cells (TEMRA) (CD45RA+CD28-) and by their intracellular cytokines (IL-17, TNFalpha, IFNgamma) using flowcytometry. Results: In 21 SSc patients with the diffuse form lower proportions of naive T-cells were found (SSc: 57.8%, HD: 64.2%). Significantly higher proportions of CCR7+ cells in CD4+ TEMRA were found in SSc patients (66.5%) compared to HD (50.4%). Patients with diffuse SSc had higher proportions of CD4+CCR6+RORgt+ T-cells (SSc: 4.8%, HD: 3.2%) with higher IL-17 production (5.6%) compared to HD (4.7%). SSc patients showed a higher production of TNFalpha (64.4%) compared to HD (54.6%), concomitantly expressing CCR7 (SSc: 46.1%, HD: 37.1%). There are nearly equal proportions of IFNgamma producing CD4 T-cells in SSc patients (10.3%) and HD (11.0%). Conclusions: Our preliminary results showed that SSc patients had a different cytokine profile in T-cells that includes abundance of CCR6+ and CCR7+ memory T-cells and more TNFalpha and IL-17 production. These findings may account for the chronic T-cell stimulation and inflammation in the pathogenesis in SSc. Disclosure of Interest: None Declared